2015
DOI: 10.4271/2015-01-2155
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Coupled Air and Particle Thermal Model for Engine Icing Test Facilities

Abstract: Air Control Volume Particle Control Volumes Air Control Volume Particle Control Volumes Fundamental Control Volume UnitSingle particle depiction (uniform particle size cloud) Full particle size distribution particle depiction (multiple particle size cloud)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…An interesting observation, consistent with previous tests, is that the wet-bulb temperature change is small when comparing cloud-off to cloud-on conditions. The interested reader is directed to Bartkus et al [9][10][11] for some modelling work which further discusses the coupling of the cloud with the thermal conditions of the flow.…”
Section: A Humidity (Twb) Sweep Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting observation, consistent with previous tests, is that the wet-bulb temperature change is small when comparing cloud-off to cloud-on conditions. The interested reader is directed to Bartkus et al [9][10][11] for some modelling work which further discusses the coupling of the cloud with the thermal conditions of the flow.…”
Section: A Humidity (Twb) Sweep Resultsmentioning
confidence: 99%
“…The most recent joint NASA and NRC test 7 in March 2012 included a traversable total air temperature (TAT) & relative humidity (RH) probe 8 which allowed measurements at tunnel centerline. Subsequent modelling showed that a decreasing air temperature was due to the energy exchange from the partial evaporation of the cloud [9][10][11] . The temperature change was sometimes as much as several degrees Celsius, which is significant for icing tests, and measurements of the cloud-on conditions are continued to the present testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analytical thermal model was initially developed (Ref. [9]) to explain the observed changes in test conditions by coupling the conservation of mass and energy equations between the icing cloud and flowing air. The model will be referred to as the Bartkus thermal model.…”
Section: Thermal Modelmentioning
confidence: 99%
“…The large temperature difference, or gradient, between the water droplet and the airflow drives the convective heat transfer between droplet and the air. More details on these interactions and thermal mechanisms are provided in Ref [9].…”
Section: Thermal Modelmentioning
confidence: 99%